2013
DOI: 10.1037/a0033367
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transparency on recognition of overlapping objects.

Abstract: Are overlapping objects easier to recognize when the objects are transparent or opaque? It is important to know whether the transparency of X-ray images of luggage contributes to the difficulty in searching those images for targets. Transparency provides extra information about objects that would normally be occluded but creates potentially ambiguous depth relations at the region of overlap. Two experiments investigated the threshold durations at which adult participants could accurately name pairs of overlapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…When the objects are transparent, although the diagnostic features are still visible, they are not necessarily easy to detect and interpret due to interference from overlapping objects. Transparency results in color combinations at regions of overlap that do not necessarily match the expectations of what the target should look like (Hillstrom, Wakefield, & Scholey, 2013). Previous studies of visual search and overlap have found that increasing overlap between objects in visual search tasks increases reaction times (RTs) and decreases response accuracy (Bravo & Farid, 2004a, 2004b, 2006; Hillstrom et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the objects are transparent, although the diagnostic features are still visible, they are not necessarily easy to detect and interpret due to interference from overlapping objects. Transparency results in color combinations at regions of overlap that do not necessarily match the expectations of what the target should look like (Hillstrom, Wakefield, & Scholey, 2013). Previous studies of visual search and overlap have found that increasing overlap between objects in visual search tasks increases reaction times (RTs) and decreases response accuracy (Bravo & Farid, 2004a, 2004b, 2006; Hillstrom et al, 2013).…”
mentioning
confidence: 99%
“…Transparency results in color combinations at regions of overlap that do not necessarily match the expectations of what the target should look like (Hillstrom, Wakefield, & Scholey, 2013). Previous studies of visual search and overlap have found that increasing overlap between objects in visual search tasks increases reaction times (RTs) and decreases response accuracy (Bravo & Farid, 2004a, 2004b, 2006; Hillstrom et al, 2013). Here, we manipulated overlap at the level of the item and included high levels of overlap (up to 90% of an object could overlap with another).…”
mentioning
confidence: 99%
“…The configuration of contour junctions, for instance, frequently signals the relation between two surfaces. Whereas T-junctions typically imply occlusion ( Figure 3A ; Rubin, 2001 ; Hillstrom et al, 2013 ), contours aligned in the way of an X-junction (see Figure 3B ) indicate transparency ( Metelli, 1974b ; Watanabe and Cavanagh, 1993 ; Rubin, 2001 ; Hillstrom et al, 2013 ). In a similar way, edge assignment can affect transparency perception ( Nakayama et al, 1989 ; Qiu and von der Heydt, 2007 ).…”
Section: Transparent Barriers: a Visual Challengementioning
confidence: 99%
“…(B) Transparent square and circle, with X-junctions marked by dashed circles. Source: From Hillstrom et al (2013) . Copyright 2013 American Psychological Association; reprinted by permission.…”
Section: Transparent Barriers: a Visual Challengementioning
confidence: 99%
“…In addition, these assessments claim clinical utility and sensitivity to change in relation to chronological age or developmental level of the norming group. Intervention ABSS is a client-driven intervention that assists with the remediation of perceptual and bilateral integration difficulties through enhancing children's understanding of the space beyond the initial visual plane as well as the symmetry of objects that are found within nature (e.g., on the human body)(Hillstrom, Wakefield, & Scholey, 2013;Schiano, McBeath, & Chambers, 2008). Inthis regard, the ABSS is comprised of a bilateral board, an arc representing the intervention space, 24 geometric shapes, 25 marbles of varying size, a pointer, a cylinder, stoppers, a number of toys to demonstrate symmetry, and a manual with examples of how the shapes are manipulated to build designs in a two or three dimensional plane.…”
mentioning
confidence: 99%